Improving treatments for psychotic disorders: beyond cognitive behaviour therapy for psychosis. Issue 1 (2nd January 2021) - Nelson, B.; Torregrossa, L.; Thompson, A.; Sass, L.A.; Park, S.; Hartmann, J.A.; McGorry, P.D.; Alvarez-Jimenez, M.
ABSTRACT: More effective treatments for people with psychotic disorders are urgently required. Here, we make three suggestions for progress: 1. Targeting the disorders' core phenomenological features ('phenomenological phenotype'), 2. Addressing social disconnection, isolation and loneliness, and 3. Leveraging 'hot' cognitions and using symptom capture approaches that combine psychotherapy with advances in technology and neuroscience.